Access to catheterisation facilities in patients admitted with acute coronary syndrome: multinational registry study. Issue 7489 (21st January 2005) - Van de Werf, Frans; Gore, Joel M; Avezum, Álvaro; Gulba, Dietrich C; Goodman, Shaun G; Budaj, Andrzej; Brieger, David; White, Kami; Fox, Keith A A; Eagle, Kim A; Kennelly, Brian M
Abstract: Objective To investigate the relation between access to a cardiac catheterisation laboratory and clinical outcomes in patients admitted to hospital with suspected acute coronary syndrome. Design Prospective, multinational, observational registry. Setting Patients enrolled in 106 hospitals in 14 countries between April 1999 and March 2003. Participants 28 825 patients aged > 18 years. Main outcome measures Use of percutaneous coronary intervention or coronary artery bypass graft surgery, death, infarction after discharge, stroke, or major bleeding. Results Most patients (77%) across all regions (United States, Europe, Argentina and Brazil, Australia, New Zealand, and Canada) were admitted to hospitals with catheterisation facilities. As expected, the availability of a catheterisation laboratory was associated with more frequent use of percutaneous coronary intervention (41% v 3.9%, P < 0.001) and coronary artery bypass graft (7.1% v 0.7%, P < 0.001). After adjustment for baseline characteristics, medical history, and geographical region there were no significant differences in the risk of early death between patients in hospitals with or without catheterisation facilities (odds ratio 1.13, 95% confidence interval 0.98 to 1.30, for death in hospital; hazard ratio 1.05, 0.93 to 1.18, for death at 30 days). The risk of death at six months was significantly higher in patients first admitted to hospitals with catheterisation facilities (hazard ratio 1.14, 1.03 to 1.26), as was the risk of bleeding complications in hospital (odds ratio 1.94, 1.57 to 2.39) and stroke (odds ratio 1.53, 1.10 to 2.14). Conclusions These findings support the current strategy of directing patients with suspected acute coronary syndrome to the nearest hospital with acute care facilities, irrespective of the availability of a catheterisation laboratory, and argue against early routine transfer of these patients to tertiary care hospitals with interventional facilities.